Representasi Profesi Jurnalis dalam Novel Bulan Terbelah di Langit Amerika “Kajian Sosiologi Sastra” - Siti Nur Azizah; Handika Saputra; Nanda Berlian Dwi Maulita; Mohamad Afrizal (Pusat Riset dan Inovasi Nasional, 2024)
This article aims to analyze the representation of the journalist profession in the novel Bulan Terbelah di Langit Amerika by Hanum Salsabiela Rais and Rangga Almahendra. Through Alfred Schutzl's representation theory approach, this study explores how the journalist profession is depicted in facing ethical, social, and professional challenges. The main focus of this study is on the character of Hanum who struggles to find sources, compose articles with sensitive themes, and face moral dilemmas amidst the issue of Islamophobia after the 9/11 tragedy. This study uses a qualitative method with text analysis to reveal the journalism process that Hanum undergoes as a reflection of the dynamics of the profession in the real world. The findings show that the journalist profession is depicted as a job that requires integrity, courage, and the ability to bridge different perspectives in stressful situations. This article is expected to provide insight into how literary works can represent the journalist profession and inspire further discussion on the role of journalism in shaping public perception.